The Role of Tax in Managing Offshore Fishing Activities - An Application of Bioeconomic Model - Nguyen, Viet Hanh (ĐHKT, 2016)
The paper's purpose is to light up the role of tax in managing offshore fishing activities. It was conducted by considering two management regimes. Each management regime is linked to two policy goals namely, the maximum sustainable biomass yield and maximum sustainable economic yield goal. The Verhulst Schaefer model and Wachsman model were employed to estimate the biological parameters and economic analysis.